CB1R activates the epilepsy-associated protein Go to regulate neurotransmitter release and synaptic plasticity in the cerebellum - Choi, Jung-Mi (2024)
GNAO1 encodes the alpha subunit of the heterotrimeric Go protein. Despite being the most abundant G protein at synapses, the role of Go in the brain remains unclear, primarily because of the high mortality associated with developmental and epileptic encephalopathy (DEE) 17 in Gnao1 mutated animals. Here, we conducted proteomic analyses with a brain synaptosomal fraction to investigate the Go-interactome and then generated a non-DEE model using Gli1CreERT2 mice to selectively knockout (KO) the presynaptic Gαo within cerebellum. Our findings revealed that Gαo interacts with multiple proteins involved in neurotransmitter release, as well as cannabinoid receptor type 1 (CB1R), a key Gi/o-coupled receptor in presynaptic terminals. In Gnao1 KO mice, synapse formation was reduced in the cerebellum with a concomitant reduction in depolarization-induced suppression of excitation, a manifestation of CB1R-mediated synaptic plasticity found in the cerebellum. These mice displayed motor deficits in rotarod, grip strength, gait, and beam balance tests. Our results suggest that Go plays a critical role in regulating neurotransmitter releases at the presynaptic terminals and its absence in the entire brain may contribute to DEE pathogenesis. This study also provides valuable insights into the signaling pathways in the brain from a Go-dependent perspective.